PENGARUH PERTUMBUHAN EKONOMI, DANA ALOKASI UMUM, PENDAPATAN ASLI DAERAH, SISA LEBIH PELAKSANAAN ANGGARAN DAN JUMLAH PENDUDUK TERHADAP BELANJA MODAL PADA PROVINSI DI INDONESIA - SAHALA PURBA; GRACESIELA YOSEPHINE SIMANJUNTAK (LP2MTBM MAKARIOZ, 2019)
The purpose of testing is to determine the effect of Economic Growth, General Allocation Funds (DAU), Regional Original Revenues (PAD), Over Time Budget Implementation (SiLPA) and the total population on Capital Expenditures in Indonesian Provinces. In this study, the sample was selected using the method purposive sampling and the data were tested using multiple regression analysis. The 2013-2015 provincial financial reports in Indonesia constitute the population in this study.The analysis results obtained that partially the General Allocation Fund (DAU), Regional Original Revenue (PAD), and the Total Population have a significant negative effect on Capital Expenditures in the Provinces in Indonesia, while the economic growth and the excess of the Execution of the Budget (SiLPA) have no effect and no significantly to Capital Expenditures in Indonesian Provinces. Simultaneously Economic Growth, General Allocation Funds, Regional Original Receipts, More Budget Implementation, and Population Amount to Capital Expenditures have an effect on Capital Expenditures in Indonesian Provinces.